2007
DOI: 10.1111/j.1872-034x.2007.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of symptomatic gastroesophageal reflux disease on quality of life of patients with chronic liver disease

Abstract: The QOL of chronic liver disease patients with symptomatic GERD was impaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…Previous studies have reported lower QOL in patients with cirrhosis compared with normal controls and liver disease patients without cirrhosis. However, most of those studies were limited by small sample sizes,19, 24, 25 use of single‐center samples,13, 26–30 disease‐specific measures,31, 32 or the inclusion of univariable analysis only 9, 26–28, 33. Studies that have used surrogate measures of cirrhosis, such as presence of splenomegaly or patient self‐report of cirrhosis, suggested that cirrhosis may be independently associated with lower QOL, in a variety of other liver diseases 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported lower QOL in patients with cirrhosis compared with normal controls and liver disease patients without cirrhosis. However, most of those studies were limited by small sample sizes,19, 24, 25 use of single‐center samples,13, 26–30 disease‐specific measures,31, 32 or the inclusion of univariable analysis only 9, 26–28, 33. Studies that have used surrogate measures of cirrhosis, such as presence of splenomegaly or patient self‐report of cirrhosis, suggested that cirrhosis may be independently associated with lower QOL, in a variety of other liver diseases 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…They are the most abundant of the proteins in blood plasma, accounting for about 60% of the total protein corresponding to a concentration of 42 g L À 1 and provide about 80% of the osmotic pressure of blood [1]. Serum albumins have been used as a model protein for many and diverse biophysical, biochemical, and physicochemical studies [2][3][4]. As a kind of serum albumin, bovine serum albumin (BSA) has the advantages of medical importance, low cost, ready availability, and unusual ligand-binding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic liver disease patients, especially patients with portal hypertension and liver cirrhosis, have clinical manifestations, such as esophageal varices, ascites, and edema. Some studies have been conducted regarding the role of esophageal varices in the development of esophageal motor disorders and abnormal gastroesophageal reflux in these patients [7,8]. Ascites could be a factor promoting gastroesophageal reflux and it has been questioned whether or not reflux would favor the rupture of varices [9,10].…”
Section: Introductionmentioning
confidence: 99%